Germany – A Migrant Story - Seim, Andreas; Pavlović, Zoran S. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Germany stands in the focus of the "refugee crisis", which is currently causing political and social debates in Europe. In Germany, the developments are discussed controversially, often more emotionally than rationally. Here, the current German policy and discussions on this issue should not be analyzed, because they are too diverse regionally and too different according to social groups. Likewise, after the fall of 2015, when refugees of various nationalities and motivations escaped across the Mediterranean and the Balkans, came into Europe and arrived in Germany and other countries, the process is still too present to judge this more clearly from a distance. But it certainly helps to trace the historical immigration of people to Germany in order to clarify how the "Germans" deal with migrants and refugees. This report is the view on the historical dimension of migration and flight in Germany, which exerted great influence on cultural developments there. So this article should be understood rather as a first overview about the developments of "who had come, for what reasons, and under which circumstances they had become a part of German society", without claiming it to be complete or universal.